Retraction Note: Morin attenuates ferroptosis via activation of the SIRT1/p53/SLC7A11 signaling pathway to alleviate diabetic cardiomyopathy in vivo - Wang, Qingmei; Zhang, Xuanguo; Xi, Li (Experimental and Clinical Endocrinology & Diabetes)
The article Morin Attenuates Ferroptosis via Activation of the SIRT1/p53/SLC7A11 Signaling Pathway to Alleviate Diabetic Cardiomyopathy In Vivo, by Qingmei Wang, Xuanguo Zhang and Li Xi, published online on March 12, 2025 has been retracted by the Editor-in-Chief and the Publisher. Following an internal investigation by the Publisher, irregularities with respect to the submission and peer review were found. Consequently, the Editor-in-Chief therefore no longer has confidence in the results and conclusions presented in the article. The authors do not agree with this retraction.